CEMARA: Caring and Empathy Luar Biasa untuk Meningkatkan Kompetensi Sosial Guru Sekolah Luar Biasa - Tri Esti Budiningsih; Sugiariyanti Sugiariyanti; Yogi Swaraswati; Rulita Hendriyani; Arleni Arleni; Sotya Paramarta Kerta Yasa (Altruis: Journal of Community Services, 2021)
School Teachers for Students with Special-Needs (STSSN) are not only required to have high cognitive abilities, they must also have a higher level of patience and energy when dealing with students with special needs. In fact, some of them have not been able to respond appropriately the uncontrolled behavior of students with various special needs. The goals of CEMARA (Extraordinary Caring and Empathy) training are enhancing the knowledge, communication skills, and social competences of special school teachers. The training process is carried out using experiential learning with four sessions. The first session is orientation session and training contract, the second session is sharing experiences and explaining knowledge about caring skills and empathy, the third session simulates how to communicate effectively in an empathetic manner, the fourth session ends with reflection and evaluation. Seven teachers of MILB YKTM Budi Asih participated as respondents. The results of this training were the emergence of increased knowledge, communication skills and social skills among teachers. They gained new knowledge about caring and empathy, then they practiced problem analysis and positive communication skills when dealing with various special need students. The improvement of teachers’ social competences is shown by the teachers’ feedback at the end of the training